The Development of Flipbook Learning Media Assisted by Canva on Poetry Writing Material for 11th Grade Students at Madrasah Aliyah Negeri 1 Tebo - Aprimadedi, Aprimadedi; Salahuddin, Amar; Sari, Nurmala (TOFEDU: The Future of Education Journal, 2025)
This study aims to develop a flipbook learning media using the Canva application on poetry writing material. Researchers chose the Canva application because it is possible and easy to use to create flipbook learning media that are developed to look more attractive and improve student understanding, so that in the learning process students are more active and easily understand the material.This type of research was a Research and Development (R&D) research using the ADDIE development model consisting of the analysis stage (analyze), design stage (design), development stage (develop), implementation stage (implement), and evaluation stage (evaluate). This research was conducted at Madrasah Aliyah Negeri 1 Tebo in the 2024/2025 academic year. The subjects of the study were 20 class XI students. Data collection techniques used student response questionnaires, teacher responses, media expert validation sheets, content experts, and language experts.The results of the validity of flipbook learning media assisted by Canva carried out by three validators obtained an average value of 87.21% categorized as very valid. The results of teacher practicality obtained an average of 95.45% with a very practical category and an average value of student practicality of 89.33% categorized as very practical. And the average effectiveness value of 90% is categorized as very effective. It can be concluded that the flipbook learning media assisted by Canva developed by researchers is suitable for use, because it has met the valid, practical, and effective categories.